Antifungal Susceptibility of Dermatophytes Isolated From Cutaneous Fungal Infections: The Vietnamese Experience - Van, Tro Chau (Open Access Maced J Med Sci, 2019)
AIM: Evaluate the resistance of dermatophytes to systemic antifungal drugs in the Vietnamese population. METHODS: We enrolled 101 patients with cutaneous dermatophytosis at the Dermato-Venereology hospital in HCMC from August 2016 to March 2017. All the specimens were subjected to direct examination (10% KOH mount) and culture on Sabouraud dextrose agar. In vitro antifungal sensitivity testing was done on species isolated from a culture with broth microdilution method. RESULTS: Direct microscopy was positive for dermatophytes in all patients. However this pathogen was found in fungal cultures in only 61.38% of patients. The main causative agent isolated was Trichophyton spp. (90.3%), followed by Microsporum spp. (8%) and Epidermophyton spp. (1.7%). Trichophyton spp. Has shown resistance to fluconazole, griseofulvin, ketoconazole, and itraconazole in 92.9%, 46.4%, 5.4% and 1.8% of strains, respectively. All Microsporum spp. Strains were found resistant to fluconazole and griseofulvin while resistance to ketoconazole was demonstrated in only 20% of strains and none of them was resistant to itraconazole. Epidermophyton spp strains were all resistant to fluconazole, griseofulvin, ketoconazole while none of them was resistant to itraconazole. CONCLUSION: Based upon our results, Itraconazole shows the greatest probability of efficacy in the treatment of cutaneous dermatophytosis in Vietnamese patients.